PENERAPAN LEGAL MAXIMS DALAM PENYUSUNAN FATWA(Studi Fatwa MUI Tentang Penggunaan Alkohol dalam Obat-obatan dan Kosmetika) - Hasanah, Dea Uswatun (Institut Agama Islam Syubbanul Wathon Magelang, 2024)
This article explains the position and application of the Legal Maxim (qawaid fiqhiyyah) in the preparation of the MUI fatwa regarding the use of alcohol in medicinal and cosmetic products. The use of alcohol in medicinal and cosmetic products has raised questions and debate among the Muslim community, because alcohol is often associated with intoxicating drinks or khamr. So that the MUI as an institution whose role is to give fatwas in response to these questions, in the process of ijtihad to find an answer to a problem, the MUI considers instructions from the Koran, Hadith, Qiyas, Ijma, and other mu'tabar propositions. The aim of this research is to see the position and application of legal maxims (qawaid fiqhiyyah) as one of the considerations for determining the MUI fatwa regarding the use of alcohol in medicinal and cosmetic products. The resulting research results are: The use of alcohol in medicinal and cosmetic products is permitted as long as it does not come from the wine industry because it does not have a negative impact on the health of the human body. Qawaid fiqhiyyah as a legal maxim has an important position because its position in the preparation of MUI fatwas is located in the same structure as the texts (al-Qur'an and Hadith). This shows that qawaid fiqhiyyah occupies an important position in the process of determining fatwas and every existing fiqh rule. The MUI fatwa has a correlation in determining the MUI fatwa law.